1993
DOI: 10.1113/jphysiol.1993.sp019801
|View full text |Cite
|
Sign up to set email alerts
|

Membrane potential, resting calcium and calcium transients in isolated muscle fibres from normal and dystrophic mice.

Abstract: SUMMARY1. Single skeletal muscle fibres were enzymatically isolated from the flexor digitorum brevis muscles (FDB) of dystrophic mdx and control C57BL/10 mice aged 3-9 weeks. In this age range the majority (> 95%) of the mdx fibres were morphologically normal.2. There was no significant difference between the resting membrane potential (RMP) of mdx and control mice, -71P2+ 1-21 (n = 26) and -70-6+ 1-15 mV (n = 42), respectively.3. At RMP more negative than -60 mV the resting calcium (recorded with fura-2, free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
7
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 30 publications
9
63
7
1
Order By: Relevance
“…Resting membrane potential (RMP) values were in line with those described by others, with slight differences due to the different experimental conditions (26,27,35). However, RMP was not modified by ANG II in either normal and chloride-free physiological solutions (Fig.…”
Section: Effect Of In Vitro Application Of Ang II On Cable Propertiessupporting
confidence: 88%
“…Resting membrane potential (RMP) values were in line with those described by others, with slight differences due to the different experimental conditions (26,27,35). However, RMP was not modified by ANG II in either normal and chloride-free physiological solutions (Fig.…”
Section: Effect Of In Vitro Application Of Ang II On Cable Propertiessupporting
confidence: 88%
“…Initial attempts to directly measure Ca 2ϩ levels in dystrophic myofibers or myotubes led to equivocal results, with some observations supporting a general increase in total cytosolic Ca 2ϩ or subsarcolemmal Ca 2ϩ (5-10) and others showing no difference (11)(12)(13). These divergent accounts may reflect technical difficulties associated with measuring Ca 2ϩ in isolated fibers or myotubes, not to mention the uncertain physiological significance of such measurements in various ex vivo preparations or culture conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, the hypothesis that Ca 2ϩ elevations directly induce myofiber necrosis and lead to MD is controversial (2). While some groups have indeed reported global or even subsarcolemmal increases in Ca 2ϩ in dystrophic myofibers (5-10), such measurements are often technically difficult, which may be the reason why other studies have not observed a significant increase (11)(12)(13). Recent studies in transgenic (TG) mice have supported the Ca 2ϩ hypothesis of disease.…”
mentioning
confidence: 99%
“…In fact, whereas different groups (2, 13, 15) reported that the resting levels of cytosolic [Ca 2ϩ ] are higher in mdx or DMD compared with control cells and that this increase is a determinant factor leading to protease activation and subsequent muscular degeneration, other investigators (3, 4) could not confirm this difference. Controversial data have also been reported for the peak levels of [Ca 2ϩ ] c upon stimulation, some groups finding larger rises in mdx (15), others similar to controls (16), and some even reporting reductions (17). We have re-addressed this issue by using a different methodological and conceptual approach.…”
Section: Discussionmentioning
confidence: 99%